Perilaku Keuangan Mahasiswa Ditinjau Dari Gaya Hidup Hedonisme, Locus Of Control, Dan Literasi Keuangan - Nugroho, Alvian Sukma; Atmadjaja, Yovita Vivianty I.; Asyriana, Sofia (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2023)
Research Objectives: The purpose of this research is to determine the influence of a hedonistic lifestyle, locus of control, and financial literacy on students' financial behavior (Case of Students at the Faculty of Economics, University of 17 August 1945 Banyuwangi). Method: The data analysis used was multiple linear regression analysis with a sample size of 92 respondents. Research Findings: the F test states that the hedonistic lifestyle, locus of control, and financial literacy have a suitable regression model for the dependent variable, namely financial behavior. Partially, hedonistic lifestyle, locus of control, and financial literacy influence students' financial behavior. Theoretical Contribution/ Originality: This research adds to the body of knowledge by combining the lifestyle factors of hedonism, locus of control, and financial literacy in the context of students, enriching the understanding of financial behavior. Practical Implications: The results of this research can help educational institutions develop financial literacy programs. Research limitations: This research has limitations, namely the sample is small and only covers one faculty.